Activated carbon coated CNT core-shell nanocomposite for supercapacitor electrode with excellent rate performance at low temperature. (1st April 2019) - Xu, Jiang; Wang, Xi; Zhou, Xiaoshuang; Yuan, Ningyi; Ge, Shanhai; Ding, Jianning
Abstract: Low-temperature tolerant supercapacitors are very important for industrial application and scientific explorations. To date, most of the studies focused on the optimization of electrolyte system to improve low temperature performance of supercapacitors. Although some improvement has been reported, the capacitance performance decreases significantly at low temperature, especially rate performance. In this work, activated carbon coated CNT core-shell nanocomposite is fabricated to investigate the temperature dependence of capacitance. We found that the poor capacitive performance at low temperature is mainly caused by ion migration at liquid-solid interface, especially for the pores whose size is smaller than the solvated ion. When the pore size of activated carbon is large, ions can freely enter these pores and the capacitance (97 F g −1 ) measured at −70 °C is comparable with that at room temperature (108 F g −1 ). Combined with both high conductivity and short diffusion path, the composite exhibits high rate performance and long cyclic stability. This study provides a practical guide for the design of supercapacitor with high performance at low temperature.